Factors and Types of Alcohol and Tobacco Consumption in Russia - ДемьяноваАнна Андреевна (Journal of Economic Sociology, 2010)
The goal of the paper is to study the types of alcohol and tobacco consumption in Russia, as well as to analyze its determinants. The following factors are under consideration: gender, age, gender attitudes towards gender roles, income, perception of future income, education, self-assessment, respect from the others, profession, life satisfaction, income satisfaction, employment, number of working hours, religiosity, social class, trust, family status, number of children, region, type of settlement. The research is based on the 9th wave of RLMS data set.